THE IMPLEMENTATION OF LEARNING CYCLE 5E MODEL BY USING MIND MAPPING TO INCREAS THE LEARNING ACTIVITY CLASS X1 SMA 1 CEDANA ENREKANG REGENCY - Muthmainnah Muthmainnah; Ramlawati Ramlawati; Muhammad Anwar; Muhammad Fajar Marsuki (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
This research is class action research (CAR). The aim is to apply the steps of the learning cycle 5e learning model by using mind mapping to increase the learning activities of class X1 students at SMA Negeri 1 Cendana, Enrekang Regency. This research was conducted in two cycles. The results of the study show that the steps in each phase of the learning model that can improve students' learning activities are: (1) the engagement phase is carried out by associating concepts with other concepts, (2) the exploration phase is carried out by observing, asking questions and investigating by discussing , as well as recording the concepts obtained in the form of mind mapping, (3) the explanation phase is carried out by expressing the concepts that have been obtained using their own words, (4) the elaboration phase is carried out by working on problems by applying the concepts that have been obtained or expanding the concepts that have been obtained. is known, (5) the evaluation phase is carried out to determine the extent of students' knowledge of the concepts that have been studied. The learning activities of students increased from cycle I of 45.91% with an adequate predicate to 61.88% in cycle II with a good predicate.